Penerapan Model Kooperatif Tipe Student Facilitator And Explaining Untuk Meningkatkan Hasil Belajar Seni Budaya (Tari) Siswa Kelas VII Di MTs N 6 Kerinci - Ingrit Despania; Susmiarti Susmiarti (SENIMAN: Jurnal Publikasi Desain Komunikasi Visual, 2023)
This study aims to determine the differences in the learning outcomes of students taught using the Student Facilitator and Explaining type cooperative learning model with the learning outcomes of students taught with conventional learning models to improve student learning outcomes in cultural arts learning in MTsN 6 Kerinci. This type of research is a quasi-experimental study, the population in this study is all students of grade VII MTsN 6 Kerinci for the 2022/2023 school year as many as 74 people with a research sample of 2 classes, namely experimental class (VII B) and control class (VII C) with a total of 36 people, which were obtained using purposive sampling techniques. The instrument used in this study is an objective test. The technique used to test hypotheses is to use a one-way similarity test using a t-test. From the study, the average learning outcomes of students in the cognitive realm were 85.11 in the experimental class and 73.78 in the control class. Based on the analysis of the data obtained, tcount = 6.098 and ttable = 2.120 at a real level of 0.05. The result of the calculation shows that tcount > ttable, so H0 is rejected and H1 is accepted. The conclusion obtained is that "There is an improvement in cultural arts learning outcomes in class VII MTsN 6 Kerinci by using the Student Facilitator and Explaining learning model".